High-resolution image reconstruction from a low-resolution image sequence in the presence of time-varying motion blur - Patti, A.J.; Ibrahim Sezan, M.; Murat Tekalp, A. (Image Processing, 1994 International Conference on, 1994)
We address the problem of reconstruction of a high-resolution image from a sequence of low-resolution images containing arbitrary relative motion, excluding occlusion effects. We develop a formulation that simultaneously takes into account blurring due to relative sensor-object motion, sensor integration, and additive noise. We propose a POCS-based algorithm for performing the high-resolution reconstruction, and provide experimental results.< >